About Hacquet’s representation and description of the Other - Fikfak, Jurij (Hacquetia, 2015)
In his Abbidung und Beschreibung (1801 - 1808), an ethnographic viewpoint on some Slovenian, Croation and other lands, Balthasar Hacquet revealed to a large extent his fundamentally enlightened opinions about the Other and his uncivilized folk culture. He presented in a critical manner popular beliefs and the role of the church.